The Effect of Educational Units using Self-Reliant Manifold Thinking (by MOSCA MUSTIN) on Developing Transmission Skills, Transmitter Reception and Self-Confidence in Volleyball - Hasan Httaihet, Hayder; Obaid Safar, Basim (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the effect of educational units according to the crossed thinkingg of self-reliance (for Muska Mosten) in developing the skills of sending and receiving transmitters and self-confidence in volleyball, and the researcher used the experimental approach in the manner of two equal groups. And Sports Sciences - Basra University, and their number reached (20) students; they divided (10) for the control group and (10) for the experimental group. Tribal tests were applied to the research sample, and after that, the educational units of (24) educational units were applied at the rate of two units per week. after completion, From the implementation of the units, the researcher conducted the post-test, and then the results were statistically treated using the statistical program (SPSS Ver. 21), and several conclusions were reached, including: The educational units proposed by the researchers have an effect on developing the skills of the transmitter, the reception of the transmitter, and self-confidence according to the branched thinking of the third-stage students in the College of Physical Education and Sports Science at Basra University. The use of forked thinking has an effect on the development of some basic skills in the ball. In light of the researchers’ conclusion, they reached the use of forked thinking in teaching the transmitting and receiving skills in volleyball (under research) because of its high effectiveness and impact on learning. The necessity of using diversity in multimedia in the lesson of physical education because of its importance. Great for enriching the learning process and increasing motivation and desire for education while saving effort and time for the student and teacher